2019
DOI: 10.19044/esj.2019.v15n4p66
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurial Characteristics on Entrepreneurial Intention of Sudanese and Omani University Students

Abstract: This study aims to identify the level of availability of entrepreneurial characteristics among undergraduate students in some universities of Sudan and Oman, and test whether these characteristics have a significant impact on the entrepreneurial intention of these students. The study also intends to make comparison between the attitudes of students in Sudan and Oman towards establishing their businesses (self-employment). The sample of the study (n = 574) consists of students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Even though ESE has been traditionally established as a factor that best measures EI (Newman et al, 2019;Vodă & Florea, 2019), results demonstrated that ECs presented a higher influence on EI, when compared to ESE, which can be explained by the different attributes considered in ECs construct that, accurately, measures individual's entrepreneurial intention. This has been somewhat referred by Atiya et al (2019).…”
Section: Final Remarksmentioning
confidence: 98%
See 4 more Smart Citations
“…Even though ESE has been traditionally established as a factor that best measures EI (Newman et al, 2019;Vodă & Florea, 2019), results demonstrated that ECs presented a higher influence on EI, when compared to ESE, which can be explained by the different attributes considered in ECs construct that, accurately, measures individual's entrepreneurial intention. This has been somewhat referred by Atiya et al (2019).…”
Section: Final Remarksmentioning
confidence: 98%
“…EC refers to a set of attitudinal characteristics an individual has that drives one to entrepreneurship more likely than others (Moraes et al, 2018). In this fashion, ECs represent the abilities and traits an entrepreneur needs to manage a project successfully (Atiya et al, 2019). However, scholars have established different and differentiated characteristics of entrepreneurs, thus the comprehensive review of characteristics and behavior of entrepreneurs is still under development and out of this study's scope (Atiya et al, 2019;Bignotti & Le Roux, 2016;Krakauer et al, 2018).…”
Section: Entrepreneurial Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations